(untitled) (Review of Croatian History, 2021)
This work presents some legal acts passed and initiatives launched by the Croatian government the aim of which was to protect the rights of the national minorities in Croatia and reach an agreement with the representatives of the Serbs in Croatia so as to avoid armed conflict. The facts presented in this work are important in the context of any given analysis about the issue of whether the Serbs were marginalized with the change of government in Croatia in 1990 and whether their armed rebellion was caused by actions made by the Croatian government and President Tuđman or came as a result of careful planning by proponents of the idea of Greater Serbia. We used a number of documents from the archival material of the Republic of Serbian Krajina to show what had been said and written about President Tuđman in the first half of the 1990s by political and military representatives of those Croatian Serbs that rebelled against the Croatian government and participated in the armed aggression against the Republic of Croatia. We describe how the Serb leadership in the temporarily occupied areas of Croatia accused the Croatian government and Franjo Tuđman of conducting criminal and “national-Fascist” policies against the Serbs and present the facts that completely debunk the accusations. These facts include official documents issued and decisions reached by the Croatian government about protecting the national minorities in Croatia during the mandate of President Tuđman. The work ends with the conclusion that the mentioned accusations were launched for the purpose of creating a greater Serbian state by homogenizing the Serbs.